A practice of plagiarism among bachelor programme students in UiTM Samarahan Campus / Faridah Riana Abdul Bakar and Sheron Asagung - Abdul Bakar, Faridah Riana; Asagung, Sheron (2010)
Plagiarism is one of the big problems that occurred among the students in tertiary level and it is known as the behaviour in which a deliberately fraudulent attempt is made to gain undeserved intellectual credit or advantage, either for oneself or another. Thus, this study is important to survey the university students’ perception regarding the plagiarism practice. The objective for this study is to ascertain the tendency of plagiarism among students. Other than that we also want to identify the factors that lead students to involve in plagiarism. We also want to determine which gender is more likely to indulge in plagiarism. The other objective of our study is to know the relationship between plagiarism and student’s CGPA. The last objective is to encourage UiTM to amend strict rules and regulation to those students who plagiarise. This survey is a survey research quantitative data. 200 respondents from Bachelor programme in Universiti Teknologi Mara (UiTM) Sarawak Branch have been selected as the research example. A set of questionnaire had been distributed and 200 sets were returned. Not surprisingly, the practice of the plagiarism do happened in UiTM Samarahan campus.